Strategi Penegak Hukum Dalam Menanggulangi Stigma Sosial dan Kekerasan Terhadap Terduga Pelaku Santet Di Bima NTB - Andriadin; Wahyudinsyah (Universitas Bojonegoro, 2025)
The phenomenon of violence against suspected black magic perpetrators in Bima arises from the dominance of community beliefs about black magic, also reinforced by the spread of social stigma about the power of black magic itself. Objective study, wants to know the social stigma and violence against suspected black magic perpetrators in Bima, also wants to know the law enforcement strategy in overcoming the social stigma and violence against suspected black magic perpetrators in Bima. Research methods in the form of empirical law with a sociological legal approach, conceptual, and case approach. Data sources are in the form of primary data and secondary data, primary data from interviews and direct observation, secondary data consists of social norms, laws, regulations, and court decisions. Research result shows that violence based on accusations of black magic is born from the assumption of society that non-medical diseases or sudden deaths are acts of black magic. The belief of society is due to stigmatization and the dominance of established mystical beliefs. Therefore, the law enforcement strategy is to take preventive measures, provide legal education, and take firm action against perpetrators of violence suspected of black magic. In the future, there must be regulations that regulate the limitation of black magic issues, then prevention of cultural-based crimes also increases legal literacy and legal culture in society.